2020
DOI: 10.1002/rra.3704
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges for restoration of the Merced River through Yosemite Valley, Yosemite National Park, USA

Abstract: Successful river restoration requires understanding and integration of multiple disciplinary perspectives, including evaluations of past and ongoing watershed processes, local geomorphic response, and impacts unique to human activity. Nowhere is this more apparent than along the Merced River in Yosemite National Park, USA, where both an outstanding natural landscape and the consequences of over a century of human disturbances continue to interact. An intact upstream watershed highlights the importance here of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…In this, our findings are comparable to those of Booth et al (2020), who concluded that human activities such as those known to have impacted the ERV caused the Merced River to incise and partially disconnect from its historical floodplain. Specifically, they found that alluvial deposits 2–2.5 m above baseflow are now activated only half as frequently as they were a century ago.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this, our findings are comparable to those of Booth et al (2020), who concluded that human activities such as those known to have impacted the ERV caused the Merced River to incise and partially disconnect from its historical floodplain. Specifically, they found that alluvial deposits 2–2.5 m above baseflow are now activated only half as frequently as they were a century ago.…”
Section: Discussionsupporting
confidence: 91%
“…Our investigation of the ERV and more parsimonious analyses in other valleys suggests that GGL-REMs can be a valuable tool in revealing the history, valley process domains, and full restoration potential of these systems. For example, GGL-REMs correspond with surficial geologic mapping of the Yosemite Valley at a resolution comparable to that reported here for the ERV (Booth et al, 2020;Figure 10a), while a similar agreement has been found with coarser resolution geologic mapping of the Methow and Twisp River Valleys (USBR, 2009; Figure 10b), and even with General Land Office mapping of the Willamette River (Sedell & Froggatt, 1984; Figure 10c).…”
Section: Restoration Potential: What Entiatqua Was and The Entiat Riv...supporting
confidence: 83%
See 2 more Smart Citations